PERAN PENGAWAS SEKOLAH DALAM IMPLEMENTASI MANAJEMEN STRATEGIK UNTUK PENINGKATAN KOMPETENSI GURU DI SDN KABUPATEN BANJAR - Mirnawati, Sri; Suriansyah, Ahmad; Purwanti, Ratna (STKIP Pesisir Selatan, 2025)
The quality of basic education is greatly influenced by teacher competence, which in its implementation requires a strategic role of school supervisors. This study aims to examine how elementary school supervisors in Banjar Regency implement strategic management in improving teacher competence. A qualitative case study approach was used with data collection techniques in the form of in-depth interviews, observations, and document studies. The results of the study indicate that supervisors carry out their roles as strategic planners, supervisors based on mentoring, and evaluators of periodic coaching programs. A dialogic and collaborative supervision approach improves teacher professionalism, especially in learning planning. The main challenges are administrative burdens and time constraints, but can be overcome through collaboration with the principal. The strategic management implemented by supervisors has a positive impact on improving teacher competence and supports the implementation of the Merdeka Curriculum more effectively. These findings are relevant for the development of policies for fostering educational human resources in the regions.